Breathing patterns during sleep and their relationship with FEV1 in pediatric patients with cystic fibrosis residing at high altitude - Duenas-Meza, Elida; Proaños-Jurado, Nadia Juliana; Pulido-Fentanes, Sarah; Severiche-Bueno, Diego F.; Escamilla-Gil, María Isabel; Bazurto-Zapata, Maria Angelica; Jurado, Jenny Libeth; Suarez, Miguel Ricardo; Giraldo-Cadavid, Luis Fernando (Frontiers in Pediatrics, 2024)
Introduction Sleep-disordered breathing (SDB) and gas exchange disorders are common in patients with cystic fibrosis (CF). Currently, the impact of the disease on sleep patterns in patients living at high altitude and the relationship of these patterns to lung function are largely unknown. The aim of this study was to determine the frequency of SDB in children with CF aged 6–18 years and the relationship between SDB and lung function (FEV1). Methods This is an analytical cross-sectional study of children aged 6–18 years diagnosed with CF. Spirometry before and after bronchodilators and polysomnography with capnography were performed. Descriptive analysis of qualitative and continuous variables was performed. Spearman's correlation coefficient was used to determine the correlation between polysomnogram and lung function (FEV1). Results Twenty-four patients with CF were included. The mean age was 10.5 ± 3.1 years and 62.5% were male. Nine children had bronchiectasis on chest CT. The median absolute baseline FEV1 was 1,880 (1,355–2,325) ml and 98% (83%–110%) of predicted value. No significant difference in FEV1% was observed between subjects with obstructive sleep apnea (OSA) and those without OSA (P = 0.56). The prevalence of OSA was 66.7% in children younger than 13 years and 40% in children older than 13 years. The Spearman correlation coefficient between FEV1 and percentage of total sleep time with saturation less than 90% (T90) was rho −0.52 (p-value = 0.018), and between FEV1 and percentage of total sleep time with saturation less than 85% (T85) was statistically significant with rho −0.45 (p-value = 0.041). A positive correlation was observed between FEV1 and SpO2 during sleep with rho 0.53 and a statistically significant p-value (0.014). Conclusions A high prevalence of sleep apnea was found in children with CF living at high altitude, with a negative correlation between FEV1 and T90 and T85 oxygenation indices, and a positive correlation between FEV1 and SpO2 during sleep.